Kajian Pragmatik Kesantunan Berbahasa Pada Program Tonight Show Di Net Tv - Widyaningrum Kinasih Haryono (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The background of this study is the interest to study further about compliance with politeness in the maxim of respect and the maxim of modesty in the Tonight Show program on NET TV based on Leech's theory. The method used in this article is descriptive qualitative method. The problem discussed in this article is the form of compliance with politeness in the maxim of appreciation on the Tonight Show program on NET TV based on Leech's theory. The purpose of this study is to describe the form of compliance with politeness in respect maxims based on Leech's theory. The benefit of this study is for pragmatics and theoretical studies regarding language politeness through television media. Based on the results of the discussion, it was found that there were several and included in compliance with the maxim of respect and the maxim of moderation. The entire data collected is based on the amount of data, namely one maxim of respect and one maxim of modesty.